International league of associations for rheumatology recommendations for the management of psoriatic arthritis in resource-poor settings - Elmamoun, M; Eraso, M; Anderson, M; Maharaj, A; Coates, L; Chandran, V; Abogamal, A; Adebajo, AO; Ajibade, A; Ayanlowo, O; Azevedo, V; Bautista-Molano, W; et al. (Springer, 2020)
Background: Psoriatic arthritis (PsA) is a challenging heterogeneous disease. The European League Against Rheumatism (EULAR) and the Group for Research and Assessment of Psoriasis and PsA (GRAPPA) last published their respective recommendations for the management of PsA in 2015. However, these guidelines are primarily based on studies conducted in resource replete countries and may not be applicable in countries in the Americas (except Canada and USA) and Africa. We sought to adapt the existing recommendations for these regions under the auspices of the International League of Associations for Rheumatology (ILAR).